(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
In loving memory of Sam Ling Gibson, who would never accept weak excuses for ignorance This article aims to examine whether the process of expansion of access to tertiary education in Colombia, labelled the Educational Revolution by the government, has addressed inequalities that contributed to the Colombian civil conflict and threaten its reconciliation today. Using the Capabilities Approach as a framework for analysis, and referring to a combination of empirical studies, official national and supranational data and theoretical literature for evidence, it will be argued the policy has caused a stratified system that constrains non-urban and lower socio-economic people’s capabilities. Only through investment and expansion of public universities will inequalities be addressed.